2017
DOI: 10.1097/md.0000000000006407
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity, sedentary behavior, and fitness with health related quality of life in healthy children and adolescents

Abstract: Background:Health related quality of life (HRQoL) is a subjective, multidimensional and changing over time construct. When HRQoL is decreased, a child is less likely to be able to develop normally and mature into a healthy adult. Physical inactivity is a priority public health problem. Evidence suggests how even moderate levels of physical activity or high fitness levels are associated with benefits for the health in children and adolescents. The aims of this systematic review are to examine the evidence about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
0
34
0
8
Order By: Relevance
“…Furthermore, HRQOL may be favorably influenced by increased lifestyle physical activity (eg, less sedentary behaviors and increased leisure time activities) and improved functional capacity (Biddle & Asare, ; Ortega, Ruiz, Castillo, & Sjöström, ). Importantly, strong associations of physical activity and sedentary behavior with HRQOL among children and adolescents have been previously reported (Bermejo‐Cantarero et al, ; Wu et al, ). Systematic reviews and primary studies of physical activity and health outcomes have shown that children and adolescents who engaged in increased levels of habitual physical activity exhibit better physical and psychosocial well‐being than their sedentary counterparts (Bermejo‐Cantarero et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, HRQOL may be favorably influenced by increased lifestyle physical activity (eg, less sedentary behaviors and increased leisure time activities) and improved functional capacity (Biddle & Asare, ; Ortega, Ruiz, Castillo, & Sjöström, ). Importantly, strong associations of physical activity and sedentary behavior with HRQOL among children and adolescents have been previously reported (Bermejo‐Cantarero et al, ; Wu et al, ). Systematic reviews and primary studies of physical activity and health outcomes have shown that children and adolescents who engaged in increased levels of habitual physical activity exhibit better physical and psychosocial well‐being than their sedentary counterparts (Bermejo‐Cantarero et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Importantly, strong associations of physical activity and sedentary behavior with HRQOL among children and adolescents have been previously reported (Bermejo‐Cantarero et al, ; Wu et al, ). Systematic reviews and primary studies of physical activity and health outcomes have shown that children and adolescents who engaged in increased levels of habitual physical activity exhibit better physical and psychosocial well‐being than their sedentary counterparts (Bermejo‐Cantarero et al, ; Wu et al, ). Therefore, promoting physical activity among children may benefit a number of positive health outcomes among adolescents with CHD.…”
Section: Introductionmentioning
confidence: 88%
“…The practice of physical activities is related to improvement of healthrelated physical fitness (AFRS), which includes components associated with health promotion or disease prevention, better performance in daily activities, including cardiorespiratory fitness, strength and muscular resistance, flexibility and body composition. High levels of physical fitness are associated with benefits, especially for adolescents, such as positive association with academic performance [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Im Umkehrschluss existieren hohe Evidenzen zu den Effekten von körperlicher Aktivität auf die physische sowie psychische Gesundheit. So wirkt sich regelmäßige körperliche Aktivität nachweislich auf die Verringerung chronischer Erkrankungen [1], das subjektive Wohlbefinden [2] und auf ein verringertes Sterblichkeitsrisiko [3][4][5] aus. Neben anderen lebensweltlichen Ansätzen wird der Arbeitsplatz in den Gesundheitswissenschaften als ein geeignetes Setting eingestuft, um eine effektive Förderung der individuellen Gesundheit zu ermöglichen.…”
Section: Introductionunclassified